Pemanfaatan Edible Film Dari Limbah Nasi Aking Sebagai Bahan Pelapis Dalam Pengawetan Buah - Mubarokah N Dewi; Iqbal Maulana; Gariza Fadha; Michelle S Sesira (Proceedings Series on Physical & Formal Sciences, 2021)
The use of synthetic coatings as Food Additives consumed in the long term can damage human health. These horrible effects have paved the way for the development of edible films and natural edible coatings. One of the edible film ingredients is scorched rice which can be used as a coating in fruit preservation. However, the use of this edible film on food ingredients has some problems, especially its mechanical properties which tend to be fragile (not flexible). This article examines the mechanical characteristics of scorched rice with variations in the concentration of glycerol and carrageenan. Based on these results, it was concluded that the higher the volume of glycerol used, the percent elongation increased. The greatest elongation was obtained in the ratio of 3 g of carrageenan with 8 ml of glycerol. However, the addition of glycerol volume causes the biodegradable plastic to tear more easily. The greatest tensile strength value was obtained with a ratio of 5 g of carrageenan and 4 ml of glycerol. The edible film can prevent the spoilage of apples tested for 10 days.